Organizational and Cultural Transformation of Pesantren in Creating A Competitive Culture - Muhammad Anggung Manumanoso Prasetyo (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Pesantren has existed long before Indonesia's independence as an educational institution. Such existence is not independent of the cultural transformations that boarding schools undergo, particularly in management-related areas. The research seeks to identify the model of Pesantren's development in creating competitive advantages through the concept of culture (culture) organization. This paper employs qualitative research methods as well as surveying techniques. Based on complex diagnosis models, the study provides a brief overview of the characteristics of several pesantren in Southeast Aceh. The study's findings revealed that (1) the transformative model implemented by boarding schools in Southeast Aceh represents an integration of the main concepts, namely culture and organizational efficiency; (2) competence of leadership behaviour becomes a fundamental factor of organizational development mechanisms; and (3) professional HR contributions in creating competitive advantages. The development model proposed is a complex and holistic integration of the three concepts, with implications for future criticism. The study results also served as a solid basis for developing learner organizations. The study also provides an overview of how boarding school characteristics create competing advantages.